2012
DOI: 10.3113/fai.2012.0900
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Posterior Ankle Exposure through an Achilles Tendon-Splitting versus Posterolateral Approach

Abstract: Prospective studies will help determine if the tendon-splitting approach is a safe and clinically useful approach for surgeries in which direct access to the entire posterior ankle and subtalar joint are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…ImageJ, a public-domain Java image processing program that is freely available from the National Institutes of Health (http://rsb.info.nih.gov/ij/), has been shown to be extremely effective at measuring the area of elliptical or irregularly shaped selections. [23][24][25] The program simplifies area calculations by digitally measuring the number of pixels within a selection. As such, it may be easily be applied to the previously mentioned glenoid bone loss quantification schemes for enhancement of accuracy in measuring the area of a best-fit circle, as well as the area of the irregularly shaped bone defect.…”
Section: Discussionmentioning
confidence: 99%
“…ImageJ, a public-domain Java image processing program that is freely available from the National Institutes of Health (http://rsb.info.nih.gov/ij/), has been shown to be extremely effective at measuring the area of elliptical or irregularly shaped selections. [23][24][25] The program simplifies area calculations by digitally measuring the number of pixels within a selection. As such, it may be easily be applied to the previously mentioned glenoid bone loss quantification schemes for enhancement of accuracy in measuring the area of a best-fit circle, as well as the area of the irregularly shaped bone defect.…”
Section: Discussionmentioning
confidence: 99%
“…The approaches used were as follows: (1) a medial approach 6 with additional exposure of the ankle joint; (2) a posterolateral approach paralleling the lateral border of the Achilles tendon 14 ; and (3) the lateral transfibular approach. 2,8 The different exposures of the ankle and the subtalar joint were evaluated, with particular attention to the neurovascular structures at risk by the approach and to the extent of cartilage resection of the different joints (Figure 1).…”
Section: Approachesmentioning
confidence: 99%
“…The alternatives to the lateral transfibular approach are the modified medial approach used for triple arthrodesis 6,7,13 and the posterolateral approach paralleling the lateral border of the Achilles tendon. 3,4,14 The present study was performed to compare 2 alternative approaches 517095F AIXXX10.…”
mentioning
confidence: 99%
“…4 In a cadaveric study, it was found that the posterior midline Achilles tendon–splitting approach provided a better exposure of the posterior distal tibia and talus compared with the posterolateral approach. 14 It also allows dissection between the angiosomes to maintain blood supply to the skin. 19 Moreover, it avoids any anterior scars.…”
Section: Discussionmentioning
confidence: 99%